2015
DOI: 10.1021/acscombsci.5b00090
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Magnetic Recovery of Hits from One-Bead–One-Compound Library Screens

Abstract: On-bead screening of one-bead-one-compound (OBOC) libraries is a useful procedure for the identification of protein ligands. An important aspect of this experiment is the method by which beads that bind the target protein are separated from those that do not. Ideally, such a method would be rapid and convenient and result in the isolation of 100% of the "hits" with no false positives (beads that display compounds that are not good ligands for the target). We introduced a technique in which beads that have boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Recent efforts in the Kodadek lab have extensively characterized methods for on-bead screening that minimize the number of false positive hit beads, 35,36 a pervasive issue in screening OBOC libraries. By screening libraries with a theoretical redundancy of at least three-fold, they demonstrated that redundant hits were almost always true positive ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Recent efforts in the Kodadek lab have extensively characterized methods for on-bead screening that minimize the number of false positive hit beads, 35,36 a pervasive issue in screening OBOC libraries. By screening libraries with a theoretical redundancy of at least three-fold, they demonstrated that redundant hits were almost always true positive ligands.…”
Section: Resultsmentioning
confidence: 99%
“…S60). These results highlight the importance of the magnetic bead selection and suggest that the protocol has yet to be optimized (70). Significantly higher enrichments can probably be achieved, since magnetic bead selection can enrich yeast cells 10 4 -fold with nearquantitative yield (69).…”
Section: A Two-stage Magnetic Bead Selection/on-bead Screen Improvesmentioning
confidence: 93%
“…Positive beads are picked up manually under a stereo-microscope or by automated sorting with a COPAS instrument [99]. If the target is a protein, it can be used to decorate magnetic nanoparticles, which in turn can be used as probes to detect and isolate positive beads with magnetic bead sorting [100,101]. After positive beads are isolated, chemical decoding can be performed directly with Edman microsequencing if coding tag consists of α-amino acids [102].…”
Section: Oboc Peptide Librarymentioning
confidence: 99%